¿Dueňas o jefas de hogar? Analizando la desigualdad de género en la propiedad de activos en américa latina - Deere, Carmen Diana (2018)
Most studies that incorporate a gender dimension into the study of poverty or otherdevelopment outcomes focus on the sex of the household head. This article argues thata headship analysis gives only a partial view of gender inequality since it does not takeinto account the position of women within male-headed or dual-headed households.Drawing on household surveys for Latin America and the Caribbean, the authorspresent indicators of the degree of gender inequality in asset ownership for twelvecountries in the region that have collected individual-level data on asset ownership.Disaggregated data on asset ownership within households suggest that the distributionof property by gender is more equitable than a headship analysis alone would suggest.This different vision of relative female poverty is largely due to the fact that women inmale-headed households frequently own assets, either individually or jointly with theirspouses. The degree of gender inequality also varies according to the specific asset andamong countries. Finally, the authors suggest how household surveys could beimproved by standardizing the collection of individual-level asset data across countries.